Short- and Long-Term Antidepressant Clinical Trials for Major Depressive Disorder in Youth: Findings and Concerns - Daniel J. Safer; Daniel J. Safer; Julie Magno Zito; Julie Magno Zito (Frontiers in Psychiatry, 2019)
The diagnosis of major depressive disorder (MDD) in U.S. youth is increasing as is the rate of antidepressant medication (ADM) treatment for the disorder. Fluoxetine and escitalopram are FDA approved for the short term and maintenance treatment of MDD in youth. Placebo-controlled short-term ADM trials represent the basis for Food and Drug Administration (FDA) approval. Meta-analyses in 2007 and 2016 revealed that short-term ADM treatment of youth diagnosed with MDD resulted in no meaningful benefit for children and only marginal benefit for adolescents. Placebo substitution trials of ADM short-term responders represent the basis for FDA approval of ADM maintenance treatment. These ADM placebo substitution maintenance trials for youth with MDD are characterized by high dropout rates, a rapid withdrawal that often can follow the switch to placebo, and relapse rates that are not dissimilar from those in the natural course of the disorder. Without the evidence from problematic ADM placebo substitution trials, there is no acceptable support for the inclusion of ADM in maintenance treatment for MDD in youth.